Perencanaan Strategis Ukmk Wilayah Surabaya Dan Sekitarnya Berbasis Analisis SWOT - Lena Ellitan; Dominicus Wahyu Pradana; Ninuk Muljani; Yulius Koesworo; Robertus Sigit HL (LPPM, Universitas Katolik Widya Mandala Surabaya, 2021)
SMEs have a central role in supporting Indonesia's economic growth and providing employment for the productive age population in Indonesia. Besides that, SMEs are also the backbone of the national economy. The workshop activity with the theme of Building a SWOT Analyst-Based Strategic Planning for UKMK Surabaya City aims to maintain and develop UKMK in the Surabaya area and its surroundings. The workshops were conducted in the form of interactive lectures on matters related to making business plans and business profiles. The result of this activity is the use of a SWOT analysis as a way to identify strategic factors for MSME corporations. Using the TOWS matrix to identify a profitable niche is one way to develop a sustainable competitive advantage by using MSME strategic factors.